Fixed Point of Contractive Mappings in Cone Metric Space: Titik Tetap dari Fungsi Kontraktif pada Ruang Metrik Cone - Sitorus, Clara Magdalena; Herawati, Elvina (Journal of Mathematics Technology and Education, 2022)
The concept of a fixed point of a function is closely related to the abstract space of the function it is in, one of which is the cone metric space which is a generalization of the metric space and which was first introduced by Zhang and Huang in 2007. The cone metric space is any non-empty set that with cone metric function. The cone metric function has the domain of any non-empty set and has the codomain of an ordered Banach space. The purpose of this study is to recognize the concept of the cone metric space and its relation to the metric space, as well as to examine the fixed point theorem on the cone metric space.